The Employability of Graduates from the Chinese Language and Culture Program at Hasanuddin University in the Workforce: A Tracer Study Analysis and Its Relevance to 21st-Century Skills - Sukma; Andi Filsah Muslimat; Ria Riski Marsuki (Universitas Negeri Semarang, 2025)
This study examines the employability of graduates from the Chinese Language and Culture Program at Hasanuddin University, focusing on their career outcomes and the relevance of 21st-century skills in the workforce. Using a tracer study methodology, data was collected from 44 graduates (64.7% response rate) through surveys and interviews. The findings reveal a 72.73% employment rate, with most graduates securing roles as translators/interpreters or Chinese teachers, primarily in the private sector. Key factors influencing employability include communication skills, industry demand for Mandarin proficiency, and practical training. However, 27.27% of graduates remain unemployed, citing further education or difficulty finding suitable jobs as the primary reasons. The study highlights the need for curriculum enhancements and stronger university-industry partnerships to better align graduates' skills with labor market demands.